Kapasitas Pemerintah Desa Tanjung Harapan dalam Mencapai Status Desa Mandiri Tahun 2023 - Dhea Amanda; Kustiawan Kustiawan; Uly Sophia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Independent village status is the highest achievement in the classification of village development that shows strong social, economic and environmental resilience. Tanjung Harapan Village is the only village in Lingga Regency designated as an independent village in 2023. This study aims to analyze the capacity of the Tanjung Harapan Village Government in achieving this status using the organizational capacity theory of Horton et al. (2003), which emphasizes two main aspects, namely resources and management. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that in terms of resources, the village has adequate infrastructure and has begun to apply digital systems in administrative management, although there are still network constraints. In terms of management, the village head applies open leadership, involves the community in planning, and manages finances transparently. Capacity building of village officials is also carried out through training and periodic evaluations. In conclusion, the Tanjung Harapan Village Government has demonstrated adequate capacity to support the achievement of independent village status. However, there is a need to increase cross-sectoral cooperation and strengthen digital infrastructure to support the sustainability of village development.